The United Nations and the Russia –Ukraine Conflict - Timiyan, Jackson Tobokaye; Esekumenu , V. Clark; Sanubi, Franklins A. (Universitas Negeri Surabaya, 2024)
This study examined the United Nations and the Russia-Ukraine conflict with special focus on the mediation role of the United Nations in the face of the conflict. It painstakingly analyzed the root causes of the Russia-Ukraine Conflict from State, Regional and Global perspectives. The study adopted the historical research design which accounted for the qualitative nature of the data analysis. It also adopted the conflict theoretical framework in analyzing the variables of the study. The study found out that the realpolitik of the 5 permanent (P5) members of the Security Council has rendered the United Nations impotent in resolving conflicts. Amongst others, the study recommends that effort should be made by the United Nations to check the overbearing Cold War mentality between Russia and America. It further recommends that the UN should step down its mediation role and allow other critical actors with relatively neutral posture such as China, Turkey, India, South Africa etc to mediate with a view to achieving rapprochement between Russia and Ukraine.